Physician perceptions of integrating pharmacists into health care in Bangladesh. (4th August 2018) - Islam, Mohammed A.; Khan, Seher A.; Gunaseelan, Simi; Talukder, Rahmat M.
Abstract: Background: Pharmacy schools in Bangladesh are introducing clinical pharmacy education so that future graduates can provide patient care services in collaboration with physicians. Aims: The objective of this study is to assess physicians' attitude towards future patient‐centered roles of pharmacists in Bangladesh. Methods: An electronic survey was distributed to randomly selected physicians ( n  = 160) practising at various settings in Dhaka, Bangladesh. Results: The survey response rate was 64%. Physicians felt comfortable with the future roles of pharmacists in dispensing medications (81%), educating patients on the safe use of medications (85%), detecting/preventing prescription errors (56%), designing drug therapy regimens (78%), monitoring safety (80%) and therapeutic outcomes (62%). Conclusion: Physicians were in favor of expanded roles of the profession towards patient‐centered care. These findings may positively impact interprofessional dialogue as pharmacy education is undergoing restructuring to introduce clinical pharmacy practice in Bangladesh.